A Break in the Clouds: Connecting Community Experiences in Mosser, Cumbria. (17th January 2019) - Pillatt, Toby; Thorpe, Gemma; Marwood, Kimberley; Johnston, Robert
Abstract : This photo essay accompanies a short film, A Break in the Clouds, which explores everyday life in Mosser, a small former township on the northwest edge of the Lake District. Prompted by the historical diaries of two eighteenth-century Quaker farmers from the same area, connections were drawn between the experiences of the current farmers and those in the past. The text discusses those connections, the making of the film and how our approach was designed to democratise the research process. The images, selected by the photographer, reflect on the key themes or "spaces" that emerged during the research: home/work, land/family, landscape/weather.